Hubungan Asupan Serat dan IMT Pada Pasien Hipertensi di RSUD Tugurejo Semarang - Luthfia Dewi; Sri Rahayu Ningsih; Sufiati Bintanah (Jurnal Gizi, 2019)
Hypertension, characterized by blood pressure level over 140/90mm/Hg, is medical condition caused by excessive natrium intake and overweight. Fiber intake might influence the hypertension condition. This study was aimedto explorefiber intake and nutrition status and to assess the correlation of nutrition status and the level of blood pressure ofpatients at Tugurejo Hospital Semarang. This study was a descriptive study with cros-secsional design. Twelve hypertensive subjects were interviewed directly in March–May 2019 to get the primer data. The correlation between fiber consumption and obesity was assessed by Pearson correlation andconsidered as significant at P<0.05. Of the 12 subjects, 7 subjects were obesity (58.3%), 2 subjects were overweight (16.7%), and 3 subjects were normal (25%). Furthermore, the fiber intake (g) of obesity, overweight, and normal subjects were 12.3±0.75; 8.0±1.56; and 14.6±4.23 respectively which was classified as lack. There was no correlation between fiber consumption and excessive body weight (P=0.261; r=-0.352). There was no correlation between level of blood pressure and excessive body weight(P=0.480; r=-0.256). The number of samples in this study were literally small which might related to the statistical analysis significancy. Keywords: fiber, obesity, hypertension